Investigating Pharmacists’ Perceived Organizational Performance through Learning and Innovation under the Moderating Role of Power Distance - Naz, Kiran; Sarmad, Muhammad; Rasheed, Irum; Rasheed, Irum; Khan, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the perspective of pharmacists regarding organizational learning and innovation for perceived organizational performance under the moderating role of power distance. The said investigation was pursued under knowledge based theory to analyze the need of new learning and innovation in pharmaceutical sector for dissemination of knowledge for effective performance in accordance with culture. The data was collected through adopted questionnaire in time lags from pharmacists working at middle tier of pharmaceutical sector across major cities of Pakistan. Out of 400 distributed questionnaires, 271 were completely responded. Statistical techniques were applied through SPSS and SMART PLS soft wares to analyze the respondents’ feedback. The results showed that organization learning and organization innovation were positively related to perceived organizational performance. Subsequently, power distance culture moderated the hypothesized relationships. Thus, implications were made for managers and policy makers in order to further strengthen the pharmaceutical sector of Pakistan.